Aerogel interface evaporator based on two-dimensional lamellar liquid crystal graphene oxide and preparation method of aerogel interface evaporator
By using spraying method to load liquid crystal graphene oxide in solar evaporators and irradiate with xenon lamps, the problems of low evaporation rate and high energy consumption are solved, efficient seawater desalination and reduced heat loss.
Patent Information
- Application Number
- CN202411951474.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Existing solar evaporators have problems with low evaporation rate, large heat loss and salt deposition in seawater desalination, and external energy is required during the preparation process, resulting in high energy consumption.
The liquid crystal graphene oxide was loaded on the aerogel by spraying, and the reduction film was irradiated with a xenon lamp to adjust the concentration and load amount of the liquid crystal graphene oxide to prepare an efficient aerogel interface evaporator.
Increases the evaporation rate, reduces heat loss, reduces salt deposition, and simplifies the preparation process and reduces energy consumption.
Smart Images

Figure CN119750691A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solar seawater desalination, and in particular relates to an aerogel interface evaporator based on two-dimensional layered liquid crystal graphene oxide and a preparation method thereof. Background Art
[0002] Seawater desalination and sewage treatment are currently one of the most important and effective ways to solve the problem of freshwater shortage. At present, conventional seawater desalination mainly includes multi-stage distillation, multi-stage flash evaporation, compressed steam distillation, reverse osmosis membrane method, electrodialysis method, ion exchange method and freezing method, etc. These methods will lead to the consumption of a large amount of fossil fuels. Conventional sewage treatment mainly includes gravity separation method, centrifugal separation method, screening and interception method, membrane separation technology, biological oxidation pond method, anaerobic biological treatment method, biological contact oxidation method, some of these methods will lead to additional fossil energy consumption, and some of them will result in limited water quality.
[0003] Solar energy is a renewable clean energy that is inexhaustible. Therefore, using solar energy to carry out solar-driven water evaporation through light-heat conversion is one of the effective ways to achieve seawater desalination and sewage treatment to obtain clean water. Although using solar evaporators to desalinate seawater can effectively improve energy utilization, solar evaporators currently still face problems such as heat loss, low evaporation rate, and salt deposition.
[0004] The membrane based on graphene oxide (GO) has sub-nanometer interlayer channels, which can achieve efficient water transport through a combination of spatial confinement effect, capillary action and Marangoni effect, and the interlayer spacing of the GO membrane is adjustable, which can achieve screening of molecules of different sizes. In addition, GO is also an excellent photothermal material, so GO membrane has excellent application prospects in the field of solar evaporation. However, the existing methods often have stacking defects and dead zones in the process of preparing GO membranes, which affect the mass transfer of water in the membrane, thereby greatly reducing its evaporation rate and limiting its application in the field of solar evaporators. In addition, most of the existing methods are to load the two-dimensional GO membrane on other materials by vacuum filtration. Although this method can prepare GO membranes well, it requires the introduction of external energy during the preparation process. Once the amount of GO introduced is too large, when the thickness of the deposited GO membrane reaches micrometers, the required preparation time will be extremely long. Therefore, how to quickly prepare an ordered two-dimensional GO membrane is very important for improving the evaporation rate. In addition, sufficient water supply and reduced heat loss are also key factors in increasing the evaporation rate. The direct contact of the two-dimensional GO membrane with water will inevitably cause heat loss. Therefore, how to combine the two-dimensional GO membrane load with a matrix material with excellent thermal insulation and water transport properties and how to further increase the evaporation rate have become the focus of research. Summary of the invention
[0005] In view of the above problems, the purpose of the present invention is to provide an aerogel interface evaporator based on two-dimensional layered liquid crystal graphene oxide and a preparation method thereof, wherein the liquid crystal graphene oxide is loaded on a substrate material having excellent thermal insulation and water transport properties by spraying, and the concentration and loading amount of the liquid crystal graphene oxide are adjusted to achieve the preparation of an aerogel interface evaporator with a high evaporation rate, so as to solve the problems of low evaporation rate and the like of the solar interface evaporator based on graphene oxide film prepared by the existing method. The method of the present invention is easy to operate and is convenient and quick.
[0006] In view of the above purpose, the present invention first provides a method for preparing an aerogel interface evaporator based on two-dimensional layered liquid crystal graphene oxide, comprising the following steps:
[0007] (1) Preparation of liquid crystal graphene oxide (LGO): Graphite powder was added to concentrated sulfuric acid and concentrated phosphoric acid, followed by potassium permanganate and stirred at room temperature until the reaction was complete, and then a hydrogen peroxide solution was added dropwise to deionized water until the mixture turned golden yellow, and the mixture was allowed to stand for stratification, and the precipitate was collected by centrifugation, washed several times with a dilute hydrochloric acid solution and dialyzed in water to obtain LGO;
[0008] (2) Preparation of aerogel substrate: dissolving the polymer to form a gel, placing it on a copper table connected to a vacuum freeze dryer, and obtaining an aerogel by directional freeze drying;
[0009] (3) Preparation of an interfacial solar evaporator: The LGO prepared in step (1) is sprayed on the aerogel prepared in step (2), and after drying, the LGO film is reduced using a xenon lamp to obtain an interfacial solar evaporator.
[0010] In one embodiment of the present invention, the mass volume ratio of the graphite powder to concentrated sulfuric acid in step (1) is 1-4 g:120-480 mL, and the volume ratio of concentrated sulfuric acid to concentrated phosphoric acid is 8:1-10:1.
[0011] In one embodiment of the present invention, the mass fraction of the concentrated sulfuric acid in step (1) is 80-98 wt %, and the concentration of the concentrated phosphoric acid is 85-90 wt %.
[0012] In one embodiment of the present invention, the amount of potassium permanganate added in step (1) is 4 to 10 times the mass of graphite powder.
[0013] In one embodiment of the present invention, the amount of potassium permanganate added in step (1) is 2 to 3 times the mass of the graphite powder, and then 1 to 2 times the mass of the graphite powder is added every 24 hours, and the stirring time is 48 to 96 hours.
[0014] In one embodiment of the present invention, in step (1), the volume ratio of deionized water to concentrated sulfuric acid is 3-4:1, and the mass fraction of hydrogen peroxide is 30%.
[0015] In one embodiment of the present invention, the mass concentration of the dilute hydrochloric acid aqueous solution in step (1) is 1.5-2%, the dialysis time is 3-6 days, and the amount of dialysis fluid is 1.5-2L.
[0016] In one embodiment of the present invention, the polymer used in step (2) is any one or more of polyvinyl alcohol, sodium alginate, and cellulose nanofibers, the dissolution temperature is 60 to 90° C., the solvent is water, and the dissolution time is 1 h to 3 h.
[0017] In one embodiment of the present invention, the gel in step (2) is a gel formed by dissolving polyvinyl alcohol and glutaraldehyde in water, the mass volume ratio of the polyvinyl alcohol to glutaraldehyde is (0.3-1) g: (0.04-0.25) mL, and the volume ratio of the glutaraldehyde to water is 0.04-0.25:3-10.
[0018] In one embodiment of the present invention, the gel in step (2) is a gel formed by mixing polyvinyl alcohol, cellulose nanofibers and water, the mass ratio of the polyvinyl alcohol to the cellulose nanofibers is 2-6:1-4, and the mass ratio of the polyvinyl alcohol to water is (0.2-0.6):(3-10).
[0019] In one embodiment of the present invention, the gel in step (2) is a gel formed by sodium alginate, calcium chloride and water, the mass volume ratio of the sodium alginate and calcium chloride is (0.3-1) g: (0.3-0.8) mL, and the volume ratio of the calcium chloride and water is 0.3-0.8:3-10.
[0020] In one embodiment of the present invention, the freezing temperature in step (2) is -100 to -60°C, the freezing time is 2 to 5 hours, the vacuum degree of the vacuum freeze dryer is 0.1 to 20 Pa, and the drying time is 48 to 96 hours.
[0021] In one embodiment of the present invention, the concentration of LGO used in step (3) is 1 to 20 mg / mL, preferably 10 to 20 mg / mL, and the surface area of the aerogel is 10 to 15 cm -2 , the volume of LGO is 0.5~2mL.
[0022] In one embodiment of the present invention, the spraying distance in step (3) is 10 to 15 cm, and the spraying pressure is 30 to 50 bar.
[0023] In one embodiment of the present invention, the drying temperature in step (3) is 45-60° C. and the drying time is 5-10 hours.
[0024] In one embodiment of the present invention, the xenon lamp reduction light intensity in step (3) is 1 to 3 KW / m 2 ·h, the reduction time is 2 to 10h.
[0025] The present invention prepares and provides an aerogel interface evaporator based on two-dimensional layered LGO based on the above method.
[0026] The present invention discloses an application of an aerogel interface evaporator based on two-dimensional layered LGO prepared by the above method in the field of solar seawater desalination.
[0027] The beneficial effects of the present invention are:
[0028] (1) The present invention adopts a spraying method to load liquid crystal graphene oxide on aerogel, and uses a xenon lamp to reduce the LGO film to prepare an interfacial solar evaporator. By spraying liquid crystal graphene oxide on the aerogel, the graphene oxide dispersion can quickly form an LGO film under the irradiation of a xenon lamp, which greatly shortens the preparation time of the solar evaporator. In addition, the xenon lamp irradiation reduction helps to increase the photothermal conversion performance and evaporation rate of the evaporator.
[0029] (2) The present invention helps to control the oxidation rate of graphene by adding potassium permanganate in batches to prepare large-sized LGO nanosheets. As the LGO concentration increases, the interaction between layers is enhanced to form a liquid crystal ordered phase, which can effectively improve the stacking defects and dead zones existing in the film preparation process, increase the transmission rate of water molecules and inhibit salt deposition.
[0030] (3) The aerogel material prepared by the method of the present invention has a vertical pore structure, which can effectively promote water transmission capacity, so that water is transmitted to the evaporation interface and heat loss is reduced.
[0031] (4) The aerogel evaporator with a two-dimensional ordered photothermal interface constructed by the method of the present invention exhibits excellent evaporation performance, with an evaporation rate of up to 3.15 kg / m 2 ·h, which is conducive to alleviating the problems of water shortage and energy shortage, and has broad application prospects in the field of solar desalination. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a scanning electron microscope image of the aerogel prepared in Example 1 of the present invention.
[0033] Figure 2 This is a scanning electron microscope image of the two-dimensional ordered photothermal interface layer prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0035] Test method for evaporation rate:
[0036] The parameters are selected under the irradiation of a xenon lamp with an intensity of 1 sun, with water as the evaporating liquid. The interface evaporator is placed in polystyrene foam and then placed in a beaker containing the evaporating liquid. The mass loss in the beaker is recorded every 5 minutes at 25°C, and the evaporation rate and evaporation efficiency are calculated by the formula.
[0037] Water evaporation rate formula:
[0038]
[0039] Among them, m0 is the initial mass of the device, m1 is the mass of the device after evaporation for a certain time, s represents the projected area of the aerogel evaporator, and t is the sunlight exposure time.
[0040] Evaporation efficiency formula:
[0041]
[0042] Where v is the water evaporation rate measured by the solar evaporator (kg / m 2 h, total water evaporation minus natural evaporation without sunlight); Q i The sunlight intensity provided per hour (1KW / m 2 ·h), H LV It is the total enthalpy change of liquid-gas phase transition (2257KJ / kg).
[0043] Example 1
[0044] A method for preparing an aerogel interface evaporator based on two-dimensional layered LGO comprises the following steps:
[0045] (1) Preparation of liquid crystal graphene oxide (LGO): 2g of 325 mesh flake graphite was added to 240mL of 98wt% concentrated sulfuric acid and 27mL of 86wt% concentrated phosphoric acid, and 6g of potassium permanganate was slowly added after stirring evenly. Stirring was continued at room temperature, and 2g of potassium permanganate was added every 24h for a total of 3 times. After the reaction was completed, the mixture was slowly poured into 800mL of deionized water, and 30wt% hydrogen peroxide was added dropwise until the mixture turned golden yellow, and then allowed to stand for stratification. The precipitate was collected by centrifugation, and washed several times with 1.8% dilute hydrochloric acid and deionized water solution until the pH value was close to 5-6 to obtain LGO.
[0046] (2) 0.5 g of polyvinyl alcohol and 0.126 mL of glutaraldehyde were dissolved in 5 mL of water at 90 °C, and the bubbles were removed by vacuum. Then, 0.05 mL of 1.2 mol / L hydrochloric acid solution was added and allowed to stand for 1 h to form a gel. The gel was then frozen on a copper table at -70 °C for 2 h and vacuum freeze-dried for 48 h at a vacuum degree of 5 Pa to obtain an aerogel.
[0047] (3) 1 mL of 15 mg / mL LGO was sprayed onto the aerogel. The aerogel surface was circular with a surface area of 10 cm -2 , dried in an oven at 45°C, and then placed under a light intensity of 1KW / m 2 ·h xenon lamp for 2 h to obtain an interface evaporator.
[0048] The interface evaporator prepared in Example 1 was characterized, and the results are shown in Figures 1-2 . Figure 1 This is a scanning electron microscope image of the hydrophilic aerogel prepared in Example 1 of the present invention. The aerogel exhibits a vertical pore structure. Figure 2 This is a scanning electron microscope image of the two-dimensional photothermal interface layer prepared in Example 1 of the present invention. The cross section shows a two-dimensional layered structure, indicating that the two-dimensional layered film was successfully prepared.
[0049] Example 2
[0050] The difference between Example 2 and Example 1 is that the concentration of LGO in step (3) is different. The concentration of LGO in step (3) of Example 2 is 1 mg / mL.
[0051] Example 3
[0052] The difference between Example 3 and Example 1 is that the concentration of LGO in step (3) is different. The concentration of LGO in step (3) of Example 3 is 5 mg / mL.
[0053] Example 4
[0054] The difference between Example 4 and Example 1 is that the concentration of LGO in step (3) is different. The concentration of LGO in step (3) of Example 4 is 10 mg / mL.
[0055] Example 5
[0056] The difference between Example 5 and Example 1 is that the concentration of LGO in step (3) is different. The concentration of LGO in step (3) of Example 5 is 20 mg / mL.
[0057] The interface evaporators prepared in Examples 1 to 5 were tested. The results are shown in Table 1.
[0058] Table 1 Evaporation rate of the interface evaporator prepared in Examples 1 to 5
[0059] test LGO concentration (mg / mL) <![CDATA[Evaporation rate (kg / m 2 ·h)]]> Evaporation efficiency (%) Example 1 15 3.15 198 Example 2 1 2.48 155 Example 3 5 2.64 165 Example 4 10 2.82 177 Example 5 20 2.96 186
[0060] From the data in Table 1, it can be seen that when the total loading amount of LGO remains unchanged, with the increase of concentration, the evaporation rate and evaporation efficiency both show a trend of first increasing and then decreasing. When the LGO concentration is 15 mg / mL, the evaporation rate and evaporation efficiency reach the maximum, which are 3.15 kg / m 2 ·h and 198%.
[0061] Example 6
[0062] The difference between Example 6 and Example 1 is that the volume of LGO in step (3) is different. The volume of LGO in step (3) of Example 6 is 0.5 mL.
[0063] Example 7
[0064] The difference between Example 7 and Example 1 is that the volume of LGO in step (3) is different. The volume of LGO in step (3) of Example 7 is 1.5 mL.
[0065] Example 8
[0066] The difference between Example 8 and Example 1 is that the volume of LGO in step (3) is different. The volume of LGO in step (3) of Example 8 is 2 mL.
[0067] The interface evaporators prepared in Examples 6 to 8 were tested. The results are shown in Table 2.
[0068] Table 2 Evaporation rate of the interface evaporator prepared in Examples 6 to 8
[0069] test LGO volume (mL) <![CDATA[Evaporation rate (kg / m 2 ·h)]]> Evaporation efficiency (%) Example 6 0.5 2.86 179 Example 7 1.5 3.02 189 Example 8 2 2.95 185
[0070] It can be seen from the data in Table 2 that with the increase in the amount of LGO, the evaporation rate and evaporation efficiency first increase and then decrease.
[0071] Example 9
[0072] The difference between Example 9 and Example 1 is that the preparation method of the aerogel in step (2) is different. The preparation method of the aerogel in step (2) in Example 9 is as follows:
[0073] 0.5 g of sodium alginate was dissolved in 5 mL of water at 60 °C, and the bubbles were removed by vacuum. Then, 0.5 mL of 0.1 mol / L calcium chloride solution was added to form a gel. The gel was frozen on a copper table at -70 °C for 2 h, and vacuum freeze-dried for 48 h at a vacuum degree of 5 Pa to obtain an aerogel.
[0074] After testing, the evaporation rate of the interface evaporator prepared in Example 9 is 2.54 kg / m 2 ·h.
[0075] Example 10
[0076] The difference between Example 10 and Example 1 is that the preparation method of the aerogel in step (2) is different. The preparation method of the aerogel in step (2) of Example 10 is as follows:
[0077] 0.2 g of cellulose nanofibers were added to 2 mL of water, and 0.3 g of polyvinyl alcohol was added to 3 mL of water and dissolved at 90 °C, the bubbles were removed by vacuum, and the mixture was evenly mixed to form a gel. The gel was frozen on a copper table at -70 °C for 2 h, and vacuum freeze-dried for 48 h at a vacuum degree of 5 Pa to obtain an aerogel.
[0078] After testing, the evaporation rate of the interface evaporator prepared in Example 10 is 2.34 kg / m 2 ·h.
[0079] Embodiment 11
[0080] The difference between Example 11 and Example 1 is that the xenon lamp irradiation time in step (3) is different. The xenon lamp irradiation time in step (3) in Example 11 is 10 hours.
[0081] After testing, the evaporation rate of the interface evaporator prepared in Example 11 is 3.12 kg / m 2 ·h, indicating that the irradiation time has little effect. On the contrary, a longer irradiation time of the xenon lamp will reduce the evaporation rate.
[0082] Example 12
[0083] The difference between Example 12 and Example 1 is that in step (1), 12 g of potassium permanganate is added at one time and the reaction is carried out for 24 hours.
[0084] After testing, the evaporation rate of the interface evaporator prepared in Example 12 is 3.04 kg / m 2 ·h.
[0085] Comparative Example 1
[0086] The difference between Comparative Example 1 and Example 1 is that the xenon lamp irradiation step in step (3) is omitted.
[0087] When the interface evaporator is not irradiated with a xenon lamp, the color of the two-dimensional photothermal interface becomes lighter and the photothermal conversion performance of the resulting evaporator becomes weaker, only 86% of that after illumination.
[0088] Comparative Example 2
[0089] 1 mL of 15 mg / mL LGO was dispersed in 50 mL of aqueous solution and loaded onto a macroporous polyethersulfone membrane by vacuum filtration. The membrane preparation time was as long as 10 hours; the spray coating method can complete the membrane preparation within a few minutes.
[0090] Comparative Example 3
[0091] The difference between Comparative Example 3 and Example 1 is that the aerogel of step (2) is directly impregnated in LGO, and the thickness of the prepared two-dimensional layered film is uneven.
[0092] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing an aerogel interface evaporator based on two-dimensional layered liquid crystal graphene oxide, characterized in that: The steps include: (1) Preparation of liquid crystal graphene oxide: Graphite powder is added to concentrated sulfuric acid and concentrated phosphoric acid, followed by potassium permanganate and stirred at room temperature until the reaction is complete, and then a hydrogen peroxide solution is added dropwise to deionized water until the mixture turns golden yellow, and the mixture is allowed to stand for stratification, and the precipitate is collected by centrifugation, washed several times with a dilute hydrochloric acid solution and dialyzed in water to obtain LGO; (2) Preparation of aerogel substrate: dissolving the polymer to form a gel, placing it on a copper table connected to a vacuum freeze dryer, and obtaining an aerogel by directional freeze drying; (3) Preparation of an interfacial solar evaporator: The LGO prepared in step (1) is sprayed on the aerogel prepared in step (2), and the LGO film is reduced with a xenon lamp after drying at 45 to 60° C. for 5 to 10 hours to obtain an interfacial solar evaporator.
2. The preparation method according to claim 1, characterized in that: The mass volume ratio of the graphite powder to the concentrated sulfuric acid in step (1) is 1-4 g: 120-480 mL, the amount of potassium permanganate added is 4-10 times the mass of the graphite powder, the volume ratio of the concentrated sulfuric acid to the concentrated phosphoric acid is 8:1-10:1, the mass fraction of the concentrated sulfuric acid is 80-98 wt%, and the mass fraction of the concentrated phosphoric acid is 85-90 wt%.
3. The preparation method according to claim 1, characterized in that: In step (1), the amount of potassium permanganate added is 2 to 3 times the mass of the graphite powder, and then 1 to 2 times the mass of the graphite powder is added every 24 hours, and the stirring time is 48 to 96 hours.
4. The preparation method according to claim 1, characterized in that: In step (1), the volume ratio of deionized water to concentrated sulfuric acid is 3-4:1, the mass fraction of hydrogen peroxide is 30%, the mass concentration of dilute hydrochloric acid aqueous solution is 1.5-2%, the dialysis time is 3-6 days, and the amount of dialysis fluid is 1.5-2L.
5. The preparation method according to claim 1, characterized in that: The polymer used in step (2) is any one or more of polyvinyl alcohol, sodium alginate, and cellulose nanofibers, the dissolution temperature is 60 to 90° C., the solvent is water, and the dissolution time is 1 to 3 hours.
6. The preparation method according to claim 1, characterized in that: The gel in step (2) is a gel formed by dissolving polyvinyl alcohol and glutaraldehyde in water, wherein the mass volume ratio of the polyvinyl alcohol to glutaraldehyde is (0.3-1) g:(0.04-0.25) mL, and the volume ratio of the glutaraldehyde to water is 0.04-0.25:3-10.
7. The preparation method according to claim 1, characterized in that: The freezing temperature in step (2) is -100 to -60°C, the freezing time is 2 to 5 hours, the vacuum degree of the vacuum freeze dryer is 0.1 to 20 Pa, and the drying time is 48 to 96 hours.
8. The preparation method according to claim 1, characterized in that: The LGO concentration used in step (3) is 1-20 mg / mL, and the surface area of the aerogel is 10-15 cm -2 The LGO volume is 0.5-2 mL, the spraying distance is 10-15 cm, the spraying pressure is 30-50 bar, and the xenon lamp reduction light intensity is 1-3 KW / m 2 ·h, the reduction time is 2 to 10h.
9. An aerogel interface evaporator based on two-dimensional layered liquid crystal graphene oxide prepared according to the method according to any one of claims 1 to 8.
10. Application of the aerogel interface evaporator based on two-dimensional layered liquid crystal graphene oxide as claimed in claim 9 in the field of solar seawater desalination.
Citation Information
Patent Citations
Graphene-polypyrrole composite aerogel and preparation method and application thereof
CN105368045A
Sunlight-driven water purifying material and preparation method and application thereof
CN109351207A
Solar interface evaporation synergistic seawater desalination device
CN113929167A
Graphene composite aerogel as well as preparation method and application thereof
CN116474667A
Cited By
MOF thermal insulation layer enhanced photo-thermal composite desalination membrane and preparation method thereof
CN120885060A